Chemical transformations of push–pull fluorenones: push–pull dibenzodicyanofulvenes as well as fluorenone– and dibenzodicyanofulvene–tetracyanobutadiene conjugates. Issue 22 (19th March 2020) - Kato, Shin-ichiro; Kijima, Tomokazu; Shiota, Yoshihito; Abe, Tsukasa; Kuwako, Satoshi; Miyauchi, Hidenori; Yoshikawa, Naoki; Yamamoto, Koji; Yoshizawa, Kazunari; Yoshihara, Toshitada; Tobita, Seiji; Nakamura, Yosuke
Abstract : We report push–pull fluorenones (FOs) that can be transformed into dibenzodicyanofulvenes (DBDCFs). These FOs and DBDCFs, which contain a CC bond, can subsequently be converted into tetracyanobutadiene conjugates. Abstract : Push–pull fluorenones (FOs) were synthesized by treating a benzopentalenequinone (BPO) derivative with alkynes that bear an electron-rich aniline moiety via a regioselective [4 + 2] cycloaddition (CA) followed by a [4 + 1] retrocycloaddition (RCA). The resulting FOs were readily converted into dibenzodicyanofulvenes (DBDCFs) by treatment with malononitrile in the presence of TiCl4 and pyridine. The FOs and DBDCFs exhibit intramolecular charge-transfer (ICT) that manifests in absorptions at 350–650 nm and amphoteric electrochemical behavior. Furthermore, FOs and DBDCFs that contain a CC bond react with tetracyanoethylene in a formal [2 + 2] CA followed by a retro-electrocyclization to afford sterically congested tetracyanobutadiene (TCBD) conjugates. The substituent (H or Me) on the aromatic ring adjacent to the butadiene moiety thereby determines whether the butadiene adopts an s- cis or s- trans conformation, and thus controls the physicochemical properties of the resulting TCBDs. The TCBD conjugates exhibit ICT absorptions (≤800 nm) together with up to four reversible reduction steps.